Serum zinc levels and clinical severity of dengue infection in children - Nuke Yuliana; RM Ryadi Fadil; Alex Chairulfatah (Indonesian Pediatric Society, 2009)
Background Immunopathogenesis of dengue infection revealsthe aberrant immune response. Zinc deficiency alters immuneresponse and therefore may associated with clinical severity ofdengue infection.Objective To indentifY the relationship between serum zinc levels and clinical severity of dengue infection in children.Methods A comparative study was conducted at the Departmentof Child Health Hasan Sadikin Hospital Bandung, from Februaryto March 2007. We included children aged 14 years fulfilled theclinical criteria for dengue fever (OF), dengue hemorrhagic fever(DHF), and dengue shock syndrome (DSS) according to WHO(1997), confirmed with serologic test. Subjects were selectedconsecutively until met the sample size for each group. Serumzinc level were measured with atomic absorption spectroscopy(MS) on admission. Data were analyzed using Kruskal-Wallis andPearson chi square test. Significance was considered if P<0.05.Results The serum zinc levels were low in 47 (78.3%) children.The serum zinc level in OF, DHF, and DSS subjects were 56-81 (X±SO= 68.2±8.3) J.Lg/dL; 50-77 (X± SO = 61.6 ± 8. 7) J.Lg/dL;and35-52 (X± SO= 42.7 ± 5.4) j.tg/dL, respectively (P<0.001).The prevalence ratio ofDF to DHF and DHF to DSS were 1.444(P=0.311) and 3.353 (P=0.077), respectively.Conclusion Low serum zinc level were significantly different ineach clinical severity of dengue infection. However, low serum zinc level was not a risk factor for the development of severe dengue infection in children.